Bridge to health informatics—a 5-week intensive online program to increase diversity in health informatics - Howard, Angelita P.; Slaughter, Liane Siu; Simmonds, Consuela; McPherson, Rebecca; Kennedy, Nia; Bentley, Keisha (Frontiers in Education, 2023)
Health informatics (HI) has the potential to address health disparities and improve healthcare outcomes; however, lack of diversity in the workforce, especially at advanced levels, feeds disparities. Increasing participation from underrepresented minorities requires exposure and connection to the field and career opportunities. We created the no-cost, 5-week intensive online Bridges to Health Informatics (B2HI) program at Morehouse School of Medicine (MSM) in 2021 to connect participants from backgrounds underrepresented in HI with industry-relevant skills, professional certification, business experience, and graduate training opportunities. In 2021, our recruitment efforts attracted 65 applications, over whom 90% self-identified as African American and the majority were working adults. Among the 46 applicants accepted and enrolled, 38 (83%) completed the program. Thirteen B2HI graduates enrolled in the first offering of the online Master of Science in Health Informatics (MSHI) degree program that premiered at MSM in August 2021, the highest number for the first session of our online master’s degree programs, indicating that B2HI connects scholars with advanced training. Participants indicated immense overall satisfaction with the program and had strong positive responses for increased interest and confidence to do advanced work in the subject. Here, we detail our structure, strategy, and lessons learned from this program, which is also a success case in the generalizability of the Bridge programs designed by MSM. These programs address key factors that hinder diversity in healthcare and informatics-related fields, including awareness, access, and social support, and connect students with the next stages of training toward careers that require an advanced degree.